Recovery of nativa area used for construction of hydroelectric power station - Alves, Marlene C. [UNESP]; do Nascimento, Vagner [UNESP]; de Souza, Zigomar M. (FapUNIFESP (SciELO), 2012)
The recovery of native area used in hydroelectric power station construction is a slow process, and it requires the use of covering plant as a source of organic matter, application of nutrients and amendments as soil conditioner. Thus, this study has the objective to study the recovery of physical attribute of subsoil in a distrophic Red Latosol, used in the embankment and foundation of Hydroelectric Power Station, Ilha Solteira, São Paulo, Brazil. The design used was randomized blocks with eight treatments and four replications. The research started in 1992. The treatments consisted of green manure, pasture and soil amendment. After 13 years, total porosity, macroporosity, microporosity, bulk density, aggregate stability, resistance to penetration, organic matter of soil and dry matter of pasture production were evaluated. The adopted treatments are slowly contributing towards recovery of physical attributes of exposed subsoil. The effects of the soil recovery are reaching 0-0.10 m depth.
Recuperação em área de empréstimo usada para construção de usina hidrelétrica
Keywords: Degraded area; Green manure; Pasture